Kajian Semiotika Al-Qurâ€™an Makna Fanatisme dalam Verba â€œfarraqu diinahumâ€ Q.S. Ar-Rum: 30-37 - Fahmi, Muhamad Irsyadi (IAIN Surakarta, 2018)
This research aims to analyze the meaning of fanaticism in Quran surah Ar-Rum verse 30-37 using semiotics study. With a qualitative descriptive approach, the data in the study was the result of a literature study on the meaning of â€œfanaticismâ€ in the Quran from a variety of literature sources. The results of this study showed that â€œfanaticismâ€ in Quran surah Ar-Rum verse 30-37 has signs: 1) to the condemnation of Allah, 2) when accepting a favor or mercy of both material and non material, it will be very pleased, 3) if A calamity was struck by a moment of God, 4) if it was overwritten by a calamity caused by his own actions, in a moment of despair, 5) boasted and too strong to hold the principles of his own group.Keywords: fanatism, semiotic, tafsir.